Analysis of workload and fatigue Batik Cap workers in Sukoharjo - Lestari, Mathilda Sri; Komariah, Ainur; Suprapto, Suprapto; Sari, Maria Puspita (OPSI, 2024)
Batik is an ancestral heritage of the Indonesian people that has been preserved to this day, particularly on the island of Java. In Java, the centers of the batik industry are located in Pekalongan, Yogyakarta, Surakarta, and Sukoharjo. In Sukoharjo, there are several home industries producing batik cloth, especially in the Krendetan Sukoharjo area, which specializes in both written and stamped batik. The batik-making process in these home industries is performed manually using simple tools. A preliminary survey revealed that the batik-making process involves repetitive tasks and imposes a high workload, particularly in the batik stamping process. This study aims to determine energy expenditure during work, energy expenditure during rest, and energy consumption needs for workers in the batik industry. The research was conducted in the stamping section and the boiling process to remove wax from the fabric. The results showed that energy expenditure during the batik stamping process was 382 kcal/hour, while in the boiling process it was 402 kcal/hour. Energy expenditure during rest was 354 kcal/hour in the stamping process and 367 kcal/hour in the boiling process. Energy consumption during the stamping process was 29 kcal/hour, and in the boiling process, it was 36 kcal/hour. The required rest time for the stamping process was 7.43 minutes per 15 minutes of work, while for the boiling process it was 5 minutes per 30 minutes of work.